Clinical Practice Guideline for the management of COVID-19 in pediatrics in the Social Security of Peru (EsSalud): Synthesis of evidence and recommendations - Ortiz Chicchon, Juan Manuel (2024)
Introduction: Since the beginning of the COVID-19 pandemic, different drugs and medications have been used for the prevention and treatment of COVID-19 infection. Likewise, various investigations have been developed that evaluate the effectiveness and safety of these interventions, which have concluded that they generate more harm than benefit in patient management. For this reason, it is relevant to standardize the interventions that have proven to be effective and safe in the management of pediatric patients with COVID-19. Objective: Provide evidence-based clinical recommendations for the management of COVID-19 in pediatrics. Methods: A guideline development group (GEG) was formed that included pediatric specialists and methodologists. The GEG formulated 11 clinical questions to be answered by this CPG (Table 1). For its preparation, the GEG decided to carry out a rapid adaptation of the Guide for the care of critically ill adult patients with COVID-19 in the Americas of the Pan American Health Organization (PAHO). To formulate the recommendations, the evidence frameworks for decision (EtD) of the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology were developed. Results: This CPG addressed 11 clinical questions on management. Based on these questions, 21 recommendations were formulated (13 strong and 8 conditional), 19 good clinical practices (GCP), and 1 flow chart. Conclusion: This article summarizes the methodology and conclusions based on evidence of the CPG for the management of COVID-19 in pediatrics in EsSalud.